Self-Determination Theory and teacher instruction: A positive partnership for student performance and involvement - Perlman, Dana J. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The purpose of this study was to examine the influence of distinct motivationally-based instructional approaches on student’s game performance and involvement. 78 secondary physical education students were taught a unit of volleyball using one in either an autonomy-supportive, controlling or balanced instructional style. Using a pretest and posttest design, students were measured on their game performance and involvement during 20-minute game of volleyball. Data analysis indicated that students engaged in the autonomy-supportive context illustrated significantly higher levels of performance and involvement when compared with the other groups.